2011
DOI: 10.1021/bm101426p
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystalline Phase and Gel−Sol Transitions for Concentrated Microcrystalline Cellulose (MCC)/1-Ethyl-3-methylimidazolium Acetate (EMIMAc) Solutions

Abstract: Liquid crystalline (LC) phase transition and gel-sol transition in the solutions of microcrystalline cellulose (MCC) and ionic liquid (1-ethyl-3-methylimidazolium acetate, EMIMAc) have been investigated through a combination of polarized optical microscope (POM) observation and rheological measurements. Molecular LC phase forms at the 10 wt % cellulose concentration, as observed by POM, whereas the critical gel point is 12.5 wt % by rheological measurements according to the Winter and Chambon theory, for which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 60 publications
7
76
1
Order By: Relevance
“…Liquid crystalline structures have also been observed in cellulose-IL solutions. Kosan [61,62]. They detected the concentration threshold upon which lyotropic phases became visible by means of polarized light microscopy and oscillatory shearrheological measurements.…”
Section: Rheology Of Cellulose-il Solutionsmentioning
confidence: 99%
“…Liquid crystalline structures have also been observed in cellulose-IL solutions. Kosan [61,62]. They detected the concentration threshold upon which lyotropic phases became visible by means of polarized light microscopy and oscillatory shearrheological measurements.…”
Section: Rheology Of Cellulose-il Solutionsmentioning
confidence: 99%
“…The small frequency dependence at long time scales (low frequencies) in the PEDOT gels compared to the NP-10 and EDOT gels is consistent with the finite relaxation time (τ) usually found in surfactant gels in contrast with the near infinite relaxation time of cross-linked gels. 6162 …”
Section: Resultsmentioning
confidence: 99%
“…In 2002, Swatloski et al [23] reported that several ionic liquids (ILs) can act as direct solvents for chemically unmodified cellulose and, especially, that the use of 1-butyl-3-methylimidazolium chloride led to a viscous cellulose solution displaying optical birefringence at polymer concentrations of more than 10 wt%; however, detailed characterization of the anisotropic phase has not been made available. In 2011, it was reported that cellulose forms a molecular liquid crystalline phase in 1-ethy-3-methyimidazolium acetate solutions of >10 wt% concentration, whereas a critical gelation point was detected at a concentration slightly higher (by~2 wt%) than the anisotropic phase transition point [24].…”
Section: Fundamental Aspectsmentioning
confidence: 99%